Analyzing the distribution patterns of soybeans and rapeseeds in china under future climate change scenarios utilizing the maxent model - Yi Xiang; Zhibo Han; Shan Zhang; Feili Wei (PLoS ONE, 2026)
Soybeans and oilseed rape are the main oil crops in China. Assessing the potential geographical distributions of soybean and oilseed rape in China under global warming trends can provide a scientific basis for agricultural production. In this study, 19 climate factors were used as environmental settings based on the MaxEnt model, and the dominant factors were screened and analyzed to predict the potential distributions of soybean and oilseed rape under three climate scenarios of shared socio-economic pathways (SSP) in simulated historical and future periods and to analyze the change trends. The main conclusions were as follows: (1) There are three predominant climatic factors affecting soybeans, among which the mean temperature during the warmest season and the precipitation in the wettest month are the most significant. For rapeseed, five factors are dominant, with annual precipitation and the mean temperature during the coldest season being the primary ones. (2) It is projected that in the next nearly 50 years, the highly suitable cultivation areas for soybean and rapeseed in China will increase by at least 137,000 km² compared to historical periods, representing an increase ranging from 0.14% to 9.33%. A northward shift of cultivation boundaries primarily characterizes this expansion, while most northwest inland areas will become unsuitable for cultivation. (3) In the intermediate stage of the 21st century under the SSP126 scenario, the potential suitable areas for soybeans and rapeseed will have the largest increases of 4.28% and 8.28% respectively, indicating that the planting effect will be the best during this period. The results indicate that future climate conditions will be more suitable for the growth of soybean and rapeseed. Cultivation area selection for soybean and oilseed rape in suitable eastern areas, the selection and breeding of good varieties, and yield improvement to obtain the maximum benefits should be considered.